Preliminary earthquake report : Magnitude 4.6 Galapagos Island Region - United States Geological Survey, National Earthquake Information Center (Denver, Colorado, USA ; United States Geological Survey, National Earthquake Information Center, 2006)
http://neic.usgs.gov/neis/bulletin/neic_npan.html
Inglés
Keywords: Earthquake; Terremoto